PERANCANGAN TEKNOLOGI REVERSE OSMOSIS DENGAN MEMANFAATKAN AIR EFLUEN PENGOLAHAN AIR LIMBAH SEBAGAI BAHAN BAKU DALAM UPAYA MENGEFISIENSIKAN PEMAKAIAN AIR BERSIH DARI KAWASAN INDUSTRI MM2100 (Studi Kasus pada PT Yutaka Manufacturing Indonesia) - M. Yani Syafei; Burhan Primanintyo; Mohamad Nur Isnanda (Journal of Environmental Engineering and Waste Management, 2018)
PT. YMI is one of the automotive manufacturers for two-wheeled vehicles. As a part of the Astra Group, the company strives to become a "Green Company" through the AGC (Astra Green Company) program. One of its assessments is a 30% wastewater recycle program per month which aims to save or use clean water efficiently. The technology used for purification of effluent water from waste water treatment is by Reverse Osmosis technology with initial treatment by using Cation Resin, Activated Carbon and Micro-filtration process. The membrane used for this Reverse Osmosis system is the Filmtec 30-4040 TW / BW. The result of the application of Reverse Osmosis technology to clean water usage in PT. YMI is 34.99% which this success can be achieved due to the recycling of effluent water contributing 100%. In addition, there are also benefits obtained from the absence of effluent water into the industrial estate. Income fee earned amounted to Rp 23,591,675, - / month. For expenses (electricity usage, spare part and overtime) Rp 11.470.172, - / month so the profit earned is Rp 12.121.503, - / month. Payback Period for this R.O. system will be achieved for 24 months or 2 years.